Analytical Hierarchy Process Method as a Solution to Fiber Optic Cable Supplier Quality - Mubarok, Achmad Misbachul; Kirono, Indro; Sukaris, Sukaris; Cahyadi, Nur (Jurnal Ilmiah Manajemen Kesatuan, 2024)
PT Prima Akses Solusi Global faces challenges in selecting fiber optic cable suppliers due to a subjective evaluation process focused mainly on price and product quality. Other factors, such as delivery, service, and payment, are also crucial. To improve effectiveness, this study uses the Analytical Hierarchy Process (AHP) for a more objective approach. AHP evaluates criteria like delivery, quality, service, price, and payment. Data from questionnaires is processed using pairwise comparison weighting. The results indicate that delivery and quality are top priorities, with PT Fiberhome ranking highest (0.417), followed by PT Voksel (0.323), and PT Furukawa (0.260). The AHP method effectively enhances decision-making accuracy in supplier selection. This study recommends ongoing AHP implementation, although it is limited to fiber optic cable supplier evaluation at PT Prima Akses Solusi Global.